Procedimento metodológico para avaliação de desempenho de praças de pedágio com uso de simulação - Santos, Túlio Silveira (2017)
Toll plazas are often characterized as a potential stretch of bottleneck, due to the tariff collection process at specific points of the road. In the highway concession contract, the public manager requires compliance with efficiency measures of the concessionaire. However, not all highway concessions in Brazil have an evaluation system of performance measures related to toll plazas. In addition, the Traffic Engineering literature does not specifically approach concepts related to toll plazas. Thus, a methodological procedure was created to evaluate the performance of toll plazas and the prospects for the implementation (or not) of alternative interventions in the system. This procedure relies essentially on the simulation modeling technique and the performance measure of level of service. The procedure was applied in a case study, involving the toll plaza of Itaúna/MG, and the results indicate that the toll plaza is in good operating condition, since the level of service obtained reflects that the vehicular flow is still lower than the capacity of the system. However, the possibility of paying the toll rate through the concept of open road tolling or free-flow would present great advantages to users, in which a significant reduction of the time needed to cross the toll plaza under study can be observed.